Structural basis of the myotoxic inhibition of the Bothrops pirajai PrTX-I by the synthetic varespladib - Salvador, Guilherme H.M. [UNESP]; Pinto, Êmylle K.R.; Ortolani, Paula L.; Fortes-Dias, Consuelo L.; Cavalcante, Walter L.G.; Soares, Andreimar M.; Lomonte, Bruno; Lewin, Matthew R.; Fontes, Marcos R.M. [UNESP] (Elsevier, 2023)
Varespladib (LY315920) is a potent inhibitor of human group IIA phospholipase A2 (PLA2) originally developed to control inflammatory cascades of diseases associated with high or dysregulated levels of endogenous PLA2. Recently, varespladib was also found to inhibit snake venom PLA2 and PLA2-like toxins. Herein, ex vivo neuromuscular blocking activity assays were used to test the inhibitory activity of varespladib. The binding affinity between varespladib and a PLA2-like toxin was quantified and compared with other potential inhibitors for this class of proteins. Crystallographic and bioinformatic studies showed that varespladib binds to PrTX-I and BthTX-I into their hydrophobic channels, similarly to other previously characterized PLA2-like myotoxins. However, a new finding is that an additional varespladib binds to the MDiS region, a particular site that is related to muscle cell disruption by these toxins. The present results further advance the characterization of the molecular interactions of varespladib with PLA2-like myotoxins and provide additional evidence for this compound as a promising inhibitor candidate for different PLA2 and PLA2-like toxins.